PESANTREN EKOLOGI, KETAHANAN PANGAN, DAN ENERGI: Studi Pada Pondok Pesantren Riyadul Jannah, Pacet, Mojoketo - Segaf Baharun; Hamzah, Akhmad Fauzi; Rahmatullah, Asep (Jurnal Pendidikan Islam, 2022)
Abstract: This research will examine two important issues in relation to Islamic boarding schools. The first issue is related to ecology and the second issue is related to food and energy security, to be precise at the Riyadul Jannah Islamic Boarding School, Pacet, Mojoketo. This Islamic boarding school has long developed organic farming, such as rice, vegetables and fisheries in a well-systemized manner. Starting from the upstream (selection of planting, planting, maintenance) to the downstream (distribution) is well conceptualized. This research focuses on three research focuses, namely 1) What is the concept of ecology, food security and energy at the Riyadul Jannah Islamic Boarding School, Pacet, Mojoketo. 2) How is the ecology, food security and energy implementation of the Riyadul Jannah Islamic Boarding School, Pacet, Mojoketo? 3) How is the impact of agriculture with the concept of ecology, food security and energy for Riyadul Jannah Islamic Boarding School, Pacet, Mojoketo? This research uses a qualitative approach with a case study design. The case study design was chosen because the researcher wanted to see this contemporary phenomenon (ecology, food security and energy) as a whole.